Prevalencia de anticonceptivos en la asociación de vivienda San Juan – Banda de Shilcayo, departamento de San Martin. Perú 1992 - Chávez Panduro, Lili (1992)
In this context of crisis, poverty and social unrest no attention to the issue of population or demographic changes taking place, let alone take into account developments that will in the future, and their impact is provided as a source of social demands in health. It is clear to everyone that major changes are made by the process of urbanization with the excessive growth of cities based on the marginal urban areas, changes in population structure with a marked increase in teenage poblaci6n a high rate total fertility, and one of the most the tas rates of infant mortality and Maternal America, particularly affecting the most vulnerable social groups in rural and marginal urban areas and in the case of Maternal mortality is predominantly preventable causes. It is also clear and obvious how easily the most disadvantaged population groups in which the major health problems are concentrated are identified: children, adolescents, women and marginal urban and rural dispersed population. This is also obvious that most of the health problems affecting these groups are aggravated by factors susceptible reproductive risk can be controlled appropriate and rational use of family planning services. Given these precedents meet the expectation was generated in specific populations; the "PREVALENCE OF BIRTH IN HOUSING ASSOCIATION BAND SAN JUAN SAN MARTIN SHILCAVO DEPARTMENT OF PERU 1992.."; the same that addresses the socio cultural characteristics, reproductive behavior and trends of fertility regulation in all women of 15-49 years to guide programs in health. Family Planning and Sexual Education. We believe that the vast majority of people will have the opportunity to read this work known in some depth and probably use some method of contraception; can not say the same instead of most of the population of Peru that not only unknown, but in many cases fears and on to reject especially modern contraceptives methods. Finally we express that this work is not intended to reach definitive conclusions, but to make progress in the study institutions and persons concerned by population and health problems.